2011
DOI: 10.2119/molmed.2011.00008
|View full text |Cite
|
Sign up to set email alerts
|

Targeting S100P Inhibits Colon Cancer Growth and Metastasis by Lentivirus-Mediated RNA Interference and Proteomic Analysis

Abstract: S100P was recently found to be overexpressed in a variety of cancers and is considered a potential target for cancer therapy, but the functional role or mechanism of action of S100P in colon cancer is not fully understood. In the present study, we knocked down the gene expression of S100P in colon cancer cells using lentivirus-mediated RNA interference. This step resulted in significant inhibition of cancer cell growth, migration and invasion in vitro and tumor growth and liver metastasis in vivo. Moreover, S1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 31 publications
4
42
0
Order By: Relevance
“…129); and in breast and cervical cancer by glucocorticoids 130 . Consistent with the observation that S100P enhances the migratory capabilities of tumour cells in vitro 131 and metastasis in vivo 132134 , the majority of S100P targets are cytoskeletal regulators. S100P–mediated activation of ezrin 135 (a membrane–cytoskeleton linker protein) and Ras GTPase-activating-like protein 1 (IQGAP1; a juxtamembrane scaffolding protein that links plasma membrane receptors with downstream signalling pathways) 136 provides a direct mechanism for the regulation of tumour cell migration by S100P.…”
Section: S100 Signalling In Cancer Biologysupporting
confidence: 81%
“…129); and in breast and cervical cancer by glucocorticoids 130 . Consistent with the observation that S100P enhances the migratory capabilities of tumour cells in vitro 131 and metastasis in vivo 132134 , the majority of S100P targets are cytoskeletal regulators. S100P–mediated activation of ezrin 135 (a membrane–cytoskeleton linker protein) and Ras GTPase-activating-like protein 1 (IQGAP1; a juxtamembrane scaffolding protein that links plasma membrane receptors with downstream signalling pathways) 136 provides a direct mechanism for the regulation of tumour cell migration by S100P.…”
Section: S100 Signalling In Cancer Biologysupporting
confidence: 81%
“…Next, cell growth, colony formation and migratory assays were performed using the transduced (SW480/S100P, DLD-1, LS174T) cells. Similar to LS174T cells, DLD-1 cells express both S100P and miR-155 [22, 48]. Knockdown of miR-155 significantly decreased cell growth (Figure 6A; also see Supplementary Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Over expression of S100P is associated to poor prognosis and survival in patients with breast and lung cancer [12, 20]. On the contrary, blockage of S100P inhibits colon cancer growth and metastasis, while also improving mice survival [11, 21, 22]. Our group has previously shown that S100P expression is regulated by the PGE 2 /EP4 signaling through cAMP response element-binding protein (CREB) activation in colon cancer cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have linked S100P expression levels to cell proliferation, invasion and migration in various forms of cancer (28). …”
Section: Discussionmentioning
confidence: 99%